The link between suggestibility, compliance, and false confessions: A review using experimental and field studies. Issue 2 (24th January 2021) - Otgaar, Henry; Schell‐Leugers, Jennifer Maria; Howe, Mark L.; Vilar, Alejandra De La Fuente; Houben, Sanne T. L.; Merckelbach, Harald
Abstract: Expert witnesses and scholars sometimes disagree on whether suggestibility and compliance are related to people's tendency to falsely confess. Hence, the principal aim of this review was to amass the available evidence on the link between suggestibility and compliance and false confessions. We reviewed experimental data in which false confessions were experimentally evoked and suggestibility and compliance were measured. Furthermore, we reviewed field data of potential false confessions and their relationship with suggestibility and compliance. These diverse databases converge to the same conclusion. We unequivocally found that high levels of suggestibility (and to a lesser extent compliance) were associated with an increased vulnerability to falsely confess. Suggestibility measurements might be informative for expert witnesses who must evaluate the false confession potential in legal cases.